Pengaruh Motivasi, Kompetensi Dan Insentif Terhadap Kinerja Guru SMK Pawyatan Dhaha 1 Kota Kediri - Syindi Elva Silvina; Edy Suwasono; Heru Sutapa (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
An important aspect in the organization is human resources, human resources have a dominant role in all organizational activities, because they are the actors and determinants of achieving organizational goals. In its development, organizations face various issues in workforce management that encourage the need for professional HR management. This research aims to determine the influence of motivation, competence and incentives on the performance of teachers at SMK Pawyatan Daha 1 Kediri City, because the results of observations indicate a decline in teacher performance caused by issues of motivation, competence and incentives. This quantitative research shows that the variables of motivation, competence and incentives have a partial and simultaneous influence on performance. The coefficient of determination obtained is 0.969, meaning that 96.9% of performance is influenced by motivation, competence and incentive variables, while the remaining is influenced by other variables not examined in this research.